The Role of Online and Service Experiences in Enhancing Guest Satisfaction: A Case Study of Bali's Hospitality Industry - Ida Ayu Bellivia Nareswari; Nurdin Sobari (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: This study aims to examine the relationships between online experience, service experience, and guest satisfaction in the context of five-star hotels in Bali, Indonesia, with a focus on domestic tourists.Method: A quantitative research approach was utilized, employing Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were gathered through an online questionnaire distributed to 245 respondents who had stayed at a five-star hotel in Bali within the past 10 months. The questionnaire assessed variables such as online experience, service experience, and guest satisfaction using Likert-scale indicators.Result: The analysis revealed that online experience has a significant influence on both service experience and guest satisfaction. Additionally, service experience was found to significantly affect guest satisfaction. These findings underscore the critical role of digital interactions and high-quality service in shaping customer perceptions and fostering loyalty.Practical Implications for Economic Growth and Development: This study offers valuable insights for hotel management on enhancing digital platforms and improving service quality to elevate customer satisfaction and loyalty. By prioritizing seamless online and offline experiences, hotels can gain a competitive edge in Bali’s highly competitive hospitality market while contributing to the growth of the local tourism economy. Furthermore, these findings provide recommendations for policymakers to support digital transformation strategies in the hospitality sector, promoting sustainable tourism growth in Indonesia.